Dosage compensation of an aneuploid genome in mouse spermatogenic cells - Jansa, Petr; Homolka, David; Blatny, Radek; Mistrik, Martin; Bartek, Jiri; Forejt, Jiri (Biology of reproduction, 2014)
Autosomal trisomies and monosomies bring serious threats to embryonic development through transcriptional disarray caused primarily by the dosage effect of the aneuploid part of the genome. The present study compared the effect of a mouse-viable 30-Mb segmental trisomy on the genome-wide transcriptional profile of somatic (liver) cells and male germ cells. Although the 1.6-fold change in expression of triplicated genes reflected the gene dosage in liver cells, the extra copy genes were compensated in early pachytene spermatocytes, showing 1.18-fold increase. Although more pronounced, the dosage compensation of trisomic genes was concordant with the incidence of HORMAD2 protein and histone gammaH2AX markers of unsynapsed chromatin. A possible explanation for this includes insufficient sensitivity to detect the meiotic silencing of unsynapsed chromatin markers in the 30-Mb region of the chromosome or an earlier silencing effect of another epigenetic factor. Taken together, our results indicate that the meiotic silencing of unsynapsed chromatin is the major, but most likely not the only, factor driving the dosage compensation of triplicated genes in primary spermatocytes.
Keywords: Animals; Body Weight; Infertility, Male; chromatin; Dosage Compensation, Genetic; Mice, Inbred C57BL; Aneuploidy; genom; zvířata; Phenotype; synaptonemální komplex; Meiosis; meióza; těhotenství; kompenzace dávky (genetika); myši inbrední C57BL; tělesná hmotnost; transkriptom; mužská infertilita; Female; Trisomy; fenotyp; translokace genetická; Pregnancy; Transcriptome; Male; Spermatocytes; aneuploidie; spermatocyty; Chromatin; ženské pohlaví; játra; mužské pohlaví; trizomie; Genome; Synaptonemal Complex; Translocation, Genetic; Liver